Experimental study of batch electrocoagulation treatment of peat water in Sarawak with aluminium electrodes - Nazeri, Abdul Rahman; Allene Albania, Linus; Umang Jata, Gilan; Nurhidayah Kumar, Muhammad Firdaus Kumar; Abdullah, Yassin; Adarsh, Philip (IOP Publisher, 2020)
Peat water is commonly found in the coastal areas of Southern and Central Sarawak. About 39% of the rural communities in Sarawak are yet to receive clean water supply. As such the rural communities depend excessively rainwater and peat water for domestic usage. However, the usage of untreated peat water for domestic usage may cause harm to human health and well-being as it contains natural organic matters such as humic substances. Electrocoagulation is an environmentally friendly and simple process of water treatment. This research aims to develop a batch electrocoagulation process for treatment of peat water in Sarawak using Aluminium electrodes. The research includes the study on electrocoagulation for peat water treatment, design, and fabrication of batch electrocoagulation process using Aluminium, experimental study for optimum performances of the electrocoagulation, and economic analysis of the electrocoagulation system. Several parameters that affect the performances of the electrocoagulation system are studied such as the inter-electrode distance, number of electrodes, current density and treatment time. The performance of the system is evaluated based on the removal efficiency on turbidity, colour, Chemical Oxygen Demand (COD), Total Organic Content (TOC) and Total Suspended Solid (TSS). The system successfully removes 100% of colour, 93.35% of turbidity, 89.80% of COD, 88.22% of TOC, and 87.50% of TSS by using a current density of 25 A/m2 in 80 minutes and 8 Aluminium electrodes with inter electrode spacing of 2 cm. The final quality of treated peat water is determined to be suitable for domestic usage which falls under Class 1 water of the National Water Quality based on the parameters analyzed. The operating cost of 25 A/m2 current density for 80 minutes of treatment time by using 8 electrode plates is RM 4.32 per m3 of peat water.